An outline of American literature - Peter B High (Longman, 1998)
This book provides a complete survey of the English prose, poetry and drama of the United States from Colonial times to the 1980s. It discusses the work of major writers in their historical context, with quotations, examples and illustrations. Key features of this book are: *) a critical survey of American literature from the 1950s to the present day. *) a glossary of lierary terms. *) a table of historical and literary events.